An Assessment of the Effectiveness of Local Institutions in the Production of Exportable Pineapple in Ghana - Isaac Boakye Danquah; Irene S. Egyir (Journal of World Economy, 2023)
Pineapple is one of the important non-traditional agricultural export commodities that contributes immensely to the progress of Ghana. This study assesses the effectiveness of the local institutions in the production of pineapple for export. The study achieves this by investigating how well the Local Institutions perform their functions; both statutory and non-statutory functions based on how the institutions perceive each other’s functional performance. Primary data on the functions were obtained from thirty (30) identified local institutions categorised into five (5) namely Local Administration, Local Government, Service Organisation, Membership Organisations and Private Businesses. The data obtained were analysed using the Chi-square method of analyses. Constraints in achieving high institutional performance of the Local Institutions were ranked and the Kendall concordance coefficient was used to test the extent of agreement between the constraints. The results of the study showed that about 63 percent of the selected Local Institutions were found to be effective in the performance of their functions. The linkage among the Local Institutions was fairly strong; only 33 percent of the institutions were found to relate strongly with others. Out of the strongly linked institutions, 50 percent were found to be among the institutions that were found to be effective in the performance of their functions. Inadequate finance and poor logistics were identified as the most pressing constraints that limited the achievement of high performance of the Local Institutions. In order to be effective in performance of functions, Local Institutions need to develop innovative ways of networking with others in the pineapple subsector, especially farmers. In this way, good agricultural practices would be assured and increased production for export will be sustained.